Gallium-Nitride Semiconductor Technology and Its Practical Design Challenges in Power Electronics Applications: An Overview - Mauricio Dalla Vecchia; Simon Ravyts; Giel Van den Broeck; Johan Driesen (Energies, 2019)
This paper will revise, experimentally investigate, and discuss the main application challenges related to gallium nitride power semiconductors in switch-mode power converters. Gallium Nitride (GaN) devices are inherently gaining space in the market. Due to its high switching speed and operational switching frequency, challenges related to the circuit design procedure, passive component selection, thermal management, and experimental testing are currently faced by power electronics engineers. Therefore, the focus of this paper is on low-voltage (<650 V) devices that are used to assemble DC-DC and/or DC-AC converters to, for instance, interconnect PV generation systems in the DC and/or AC grids. The current subjects will be discussed herein: GaN device structure, the advantages and disadvantages of each lateral gallium nitride technology available, design challenges related to electrical layout and thermal management, overvoltages and its implications in the driver signal, and finally, a comprehensive comparison between GaN and Si technology considering the main parameters to increase the converters efficiency.